Quality Water Red Water (Iron) - Powell, G. Morgan; Bradshaw, Michael H.; Glanville, Thomas D. (My University, 1995)
This publication helps homeowners determine the quality of their water, and what to do if they have red water (iron).
EP26_1995_12
Keywords: EP26; Home and Family; Water; EP